Analisis, Uji Coba dan Rekontruksi Kegiatan Praktikum Melalui Lembar Kerja Peserta Didik Struktur dan Fungsi Sel: (Analysis, Testing, Recontruction Of Practical Work Through Student Worksheet Structure And Cell Function) - Anggi Angreani; Bambang Supriatno; Sri Anggraeni (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
This study contains an analysis of the Student Worksheets contained in the high school textbook / used by teachers in schools, with the aim of providing information, education or solutions to problems that have arisen in practical activities. Practicum activities are an important part of science education, so they are required to create more meaningful practicum activities. In making practicum activities more meaningful and achieving goals in accordance with Basic Competencies, one of them is by reconstructing the Student Worksheet (LKPD). This study is included in the descriptive qualitative, in which LKPD cell structure and function are made as research subjects with a sample number of 5 LKPD that refers to the SBC and Curriculum 2013. The instrument used in this research refers to: first, the form of analysis of laboratory activities where problems are emerges namely in terms of conceptual (practicum activities not in accordance with the curriculum), practical (the object does not appear clearly because the procedure is less precise) and knowledge (questions that do not construct knowledge). Second, referring to the Vee Diagram developed from Novak & Gowin. The problems that arise include practical aspects which include procedures / work steps, questions that lead to the results of the practicum. therefore there is a need to reconstruct LKPD so LKPD can be well understood and achievement in accordance with the Basic Competition (KD). Abstrak. Penelitian ini berisi tentang analisis terhadap Lembar Kerja Peserta Didik yang terdapat pada buku SMA/yang digunakan oleh guru di sekolah, dengan tujuan untuk memberikan informasi, edukasi atau solusi terhadap masalah yang selama ini muncul dalam kegiatan laboratorium. Penelitian ini termasuk ke dalam deskriptif kualitatif, dimana LKPD struktur dan fungsi sel di jadikan sebagai subjek penelitian dengan jumlah sampel 5 LKPD yang mengacu pada KTSP dan Kurikulum 2013. Instrumen yang digunakan dalam penelitan ini mengacu pada: pertama, form analisis kegiatan laboratorium dimana permasalahan yang muncul yaitu dari segi konseptual (kegiatan praktikum tidak sesuai dengan kurikulum), praktikal (objek tidak mucul secara jelas karena prosedurnya kurang tepat) dan pengetahuan (pertanyaan yang tidak mengkontruksi pada pengetahuan). Kedua, mengacu pada Diagram Vee yang dikembangkan dari Novak & Gowin. Adapun masalah yang muncul diantaranya dari segi praktikal yang meliputi prosedur/langkah kerja, pertanyaan yang mengarah ke hasil praktikum. maka dari itu perlu adanya rekontruksi LKPD agar LKPD dapat di pahami dengan baik serta pencapaian sesuai dengan Kompetesi Dasar (KD).